Who are we receiving at the university? The impact of COVID-19 on mathematics and reading learning in high school - Ortega-Barba, Claudia Fabiola; Ramírez-Pérez, Héctor X.; Méndez-Padilla Andrade, Santiago (Frontiers in Education, 2024)
We investigated how the transition to remote instruction during the COVID-19 pandemic affected the development of mathematical thinking and reading comprehension skills of High School students, based on the analysis of the results of a standardized test for entry into Higher Education. The participants were a total of N= 17942 where N1=10611 pre-pandemic applicants and N2=7331 postpandemic applicants. The pre-pandemic group considers exam results from September 2016 to June 2020. The post-pandemic group takes exam results from September 2020 up to May 2023. We conclude that emergency remote teaching decreased the average mathematical competence of entering university students by 12.8%. Similarly, emergency remote teaching decreased the average reading achievement of students entering university by 8%. Therefore, the impact of emergency remote teaching was greater on mathematics skills than on reading achievements.